Efficacy And Safety Of Low Dose Tofacitinib As Induction Therapy In Moderate To Severe Ulcerative Colitis: A Pilot Study - Sadia Ahmed; Muhammad Umar; Muhammad Kamran; Misbah Noureen; Iqra Ashraf; Javeria Khan (Journal of Rawalpindi Medical College)
Objective: The Inflammatory cascade has been the root cause of ulcerative colitis's pathogenesis, and its treatment would centre upon reducing its intensity. Tofacitinib, an orally administered micromolecule, blocks the Janus kinase (JAK) signal transducer pathway, thereby reducing mucosal inflammation. This observational study aimed to assess Tofacitinib's efficacy in relieving Ulcerative Collitis symptoms.